Osaczeni w Volksgemeinschaft. Polsko-niemiecka relacja o miłości i osamotnieniu w III Rzeszy - Grzywacz, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
The paper presents development of the Third Reich as a Volksgemeinschaft on the example of Lörrach, a small town at the Swiss- German border. In the context of world war II the authoress writes about the fate of forced labour workers, especially those from Poland. On the basis of analysis of documents and literary reports, a history of love between a Polish man and a German woman, which ended with sentencing the myoung man to death, was reconstructed. The problem of having to face and accept the Nazi past by German society is also touched.